BCL2 Family Inhibitors in the Biology and Treatment of Multiple Myeloma - Gupta VA (Dove Medical Press, 2021)
Vikas A Gupta,1 James Ackley,2 Jonathan L Kaufman,1 Lawrence H Boise1 1Department of Hematology and Medical Oncology, Winship Cancer Institute of Emory University, Emory University School of Medicine, Atlanta, GA, USA; 2Cancer Biology Graduate Program, Winship Cancer Institute of Emory University, Emory University School of Medicine, Atlanta, GA, USACorrespondence: Lawrence H BoiseDepartment of Hematology and Medical Oncology, Winship Cancer Institute of Emory University, Emory University School of Medicine, 1365 Clifton Road NE, Rm C4078, Atlanta, GA, 30322, USATel +1 404-778-4724Fax +1 404-778-5530Email lboise@emory.eduVikas A GuptaDepartment of Hematology and Medical Oncology, Winship Cancer Institute of Emory University, Emory University School of Medicine, 1365 Clifton Road NE, Rm C4090, Atlanta, GA, 30322, USATel +1 404-778-6485Fax +1 404-778-3260Email vikas.gupta@emory.eduAbstract: Although much progress has been made in the treatment of multiple myeloma, the majority of patients fail to be cured and require numerous lines of therapy. Inhibitors of the BCL2 family represent an exciting new class of drugs with a novel mechanism of action that are likely to have activity as single agents and in combination with existing myeloma therapies. The BCL2 proteins are oncogenes that promote cell survival and are frequently upregulated in multiple myeloma, making them attractive targets. Venetoclax, a BCL2 specific inhibitor, is furthest along in development and has shown promising results in a subset of myeloma characterized by the t(11;14) translocation. Combining venetoclax with proteasome inhibitors and monoclonal antibodies has improved responses in a broader group of patients, but has come at the expense of a toxicity safety signal that requires additional follow-up. MCL1 inhibitors are likely to be effective in a broader range of patients and are currently in early clinical trials. This review will cover much of what is known about the biology of these drugs, biomarkers that predict response, mechanisms of resistance, and unanswered questions as they pertain to multiple myeloma.Keywords: multiple myeloma, BCL2 family inhibitors, venetoclax